(untitled) (Global Journal of Science Frontier Research, 2012)
The study was conducted in Idanre Local Government Area of Ondo State to analyze the gender and farm technical efficiency of cocoa production(Why the research? Is it to increase productivity or to correct gender issues? State it here). The data were collected from 100 respondents with the use of structured questionnaire, which involved 54 men and 46 women cocoa farmers. The maximum likelihood estimates of frontier model of male farmers showed that only family labour and pesticides were significant while for female farmers, hired labour, insecticides and family size were significant. In addition, the inefficiency model of male cocoa farmers showed that age, education and experience were significant on technical inefficiency while female inefficiency model was significant in education, experience and age of cocoa plant. The technical efficiency showed that a lot can be done to increase the production capacity of both gender in order to make them technically efficient.